Research and Publication in Tourism and Hospitality: Possibilities in the Ecuadorian Academic Setting - Hubert B. Van Hoof (Revista Tecnológica)
University professors teach, do research and provide service to their university, the academic community, their field of study and to society in general. How much teaching and how much research they do varies greatly depending on several factors, such as the mission of the university, its funding structure (whether it is a private or a public institution), prevailing beliefs about the role of the university in society, how past research has helped in addressing society’s issues, political pressures, the expertise of its professors and the demands the university places on their time (Bok, 1982; Fairweather, 1990; Gottlieb & Keith, 1997; Birtwistle, 2003). Ecuador’s universities have historically been teaching universities, with professors spending a majority of their time on teaching-related activities and very little, if any, time on research, making it very difficult for them to create and maintain an active research portfolio (Van Hoof, Estrella, Eljuri & Torres, 2013). Yet, given these historical limitations, there are possibilities for faculty members in tourism and hospitality to do research and to publish their work in refereed, indexed publications. This article discusses the roles that research and teaching play in a university environment based on a review of relevant literature, with an emphasis on hospitality and tourism. It looks at how research and teaching effectiveness are evaluated, how the quality of publications is assessed and briefly discusses the socio-economic and political factors that are presently at work in Ecuador’s academic environments. It offers some suggestions on how research in tourism and hospitality can be conducted in Ecuador and how professors can get published, given the limited resources that are available.